Hospital Wastewater Pharmaceutical Residues and Their Impact on Community Microbial Resistance: An Epidemiological and Pharmaceutical Systematic Review - Giyantolin Giyantolin; Yuli Subiakto; Timbul Partogi Haposan Simorangkir; Widyati Widyati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Releases from healthcare facilities account for a large portion of environmental pollution, with wastewater carrying a cocktail of pharmaceutical contaminants, especially antibiotics. These compounds accelerate the accumulation of antimicrobial resistance. Objective: The study synthesizes the scientific record on the concentration, fate, and effects of pharmaceutical compounds within hospital wastewater; it foregrounds the links to growing microbial resistance and delineates the threat to public health. The review adhered to the 2020 PRISMA framework. The search strategy applied a combination of keywords (